(untitled) (Scientific journal of the Fergana State University, 2023)
Nowadays, not only men but also women are involved in various types of athletics. There are regular women’s world championships in walking, running, jumping and throwing. Working with women requires the trainer to have some knowledge of the female body. It is very important to take into account the characteristics of the female body in the design of the training process. The modern physical development, on the one hand, is improving the life of mankind, and on the other, alienating man from nature. Human activity of movement is weakened, which, due to an unfavorable environmental situation, causes great harm to the human body. A decrease in movement activity is one of the negative factors of polygyny, which is a barrier for a person to carry out productive activities. Athletics is the sport that contributes to the development of all aspects of a person, since it combines vital and common movements (walking, running, jumping, throwing). Regular exercises in athletics develop strength, speed, endurance and other qualities that are necessary for a person in the daily routine. Movement is considered as certain methods of human activity. For example, the educational activity of girls in physical education is composed of mastering the system of actions provided for by the program of educational institutions.